Implementation of sustainable hospitality by improving brand equity in tourism industry: A study case - Wiryawan, Monique; Arief, N. Nurlaela (Indonesian Journal of Multidisciplinary Science, 2023)
This study explores the connection between environmental sustainability narratives ("green narratives") and brand equity in the hospitality industry. It investigates how adopting and communicating sustainability practices affect customer-based brand equity (CBBE) using a comprehensive framework that integrates horizontal and vertical analysis and Kevin Lane Keller's CBBE model. The horizontal analysis measured how these efforts resonate with customers and influence brand perception. The vertical analysis examined the depth of sustainability initiatives, emphasizing their integration within the organization, such as eco-friendly layout, authentic local food, and excellent service. Keller's CBBE model guides the exploration of brand development stages, from identity to resonance, highlighting how green narratives impact brand recognition, significance, response, and resonance. Through this research, the author aims to uncover how green narratives shape customer perceptions and loyalty in the hospitality industry. The data for this study came from semi-structured interviews conducted as part of the qualitative research methodology. After that, the gathered data was investigated using Keller's model, vertical analysis, and horizontal analysis. Plataran's social media green narratives have a positive impact on brand equity because consumers respect and believe in companies that are committed to protecting the environment and cultural traditions. Brand resonance can be increased through active participation on social media, satisfaction surveys, loyalty plans, and creating a sense of community.